2014
DOI: 10.1111/and.12311
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histopathological evaluations of ghrelin effects following cadmium toxicity in the rat testis

Abstract: Numerous reports demonstrate that cadmium (Cd) induces oxidative stress by increasing lipid peroxidation and altering antioxidative enzymes status. Thirty male rats were subdivided into control-saline, Cd-saline and Cd-ghrelin groups. A single dose of Cd was injected to induce testicular injury and also ghrelin for 10 consecutive days to group 3. SOD activity decreased and lipid peroxidation increased by Cd administration. The mean activities of GPx and CAT as well as GSH content were lower in the Cd-saline ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Histopathological changes in testis tissue were observed when the Cd dose was higher (Bomhard et al., ; Jiang et al., ). Doses of Cd lower than was used in the present study were reported previously to induce pathological changes only when administered intraperitoneally or subcutaneously for few hours or few days in rodents (Ige et al., ; Kheradmand et al., ; Minutoli et al., ; Othman, Nada, Zaki, & Abdel Moneim, ) or when administered orally for a longer time (90‐days; El‐Refaiy & Eissa, ; 8‐weeks; Sakr & Nooh, ). In most of these studies, the testicular Cd contents increased from 1.22 to 176 μg/g (Arafa et al., ; Jahan et al., ; Koriem et al., ) depending on the duration of treatment.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Histopathological changes in testis tissue were observed when the Cd dose was higher (Bomhard et al., ; Jiang et al., ). Doses of Cd lower than was used in the present study were reported previously to induce pathological changes only when administered intraperitoneally or subcutaneously for few hours or few days in rodents (Ige et al., ; Kheradmand et al., ; Minutoli et al., ; Othman, Nada, Zaki, & Abdel Moneim, ) or when administered orally for a longer time (90‐days; El‐Refaiy & Eissa, ; 8‐weeks; Sakr & Nooh, ). In most of these studies, the testicular Cd contents increased from 1.22 to 176 μg/g (Arafa et al., ; Jahan et al., ; Koriem et al., ) depending on the duration of treatment.…”
Section: Discussionmentioning
confidence: 54%
“…Because the lipid peroxidation level was higher in the testes of Cd+EtOH‐treated animals than in the Cd‐treated rats, the antioxidant defence systems in the testes of these animals were much more disturbed compared to the Cd‐treated animals, but the testicular antioxidant defence system of the testis of these animals was able to cope with the altered oxidative balance and could not allow further peroxidative changes. It is usually reported that GSH level decreased after Cd treatment (Arafa, Mohammad, & Atteia, ; Jahan et al., ; Kheradmand, Alirezaei, & Dezfoulian, ; Koriem, Fathi, Salem, Akram, & Gamil, ; Pires et al., ). However, contrary results have observed that low Cd concentration increased GSH level, whereas high Cd concentration depleted GSH level (Gaubin et al., ), suggesting a relationship between tissue concentration of GSH and Cd (Thomas, Wofford, & Neff, ; Vogiatzis & Loumbourdis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports suggest that ghrelin prevents testicular damage induced by heat, cadmium or ionizing radiation, and a reduction of oxidative stress has been postulated as a possible mechanism, although the specific pathway remains to be fully elucidated. [19,21,44,45]. Ghrelin prevents apoptosis in a number of tissues including adipocytes, endothelial cells and others [22][23][24]46] but whether these actions are mediated through p53 has not been well-established.…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly produced in the stomach, but is also secreted by Leydig cells [15]. Ghrelin receptors are expressed in the testis [16][17][18], and ghrelin has recently been shown to prevent testicular damage in different settings [19][20][21] and to have anti-apoptotic properties in other tissues [22][23][24] but the mechanisms mediating these testicular and non-testicular effects are not fully understood. p53 was recently suggested as a key mediator of ghrelin's effects on food intake but not on its GH secretagogue activity [9].The aim of the current study was to characterize the mechanism of ghrelin and p53 action in the testis after cisplatin-induced testicular damage.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the expression of GHS-R1 in seminiferous tubules indicates that epithelium of these tubules is targets area for ghrelin activity (Kheradmand et al, 2009a(Kheradmand et al, ., 2009b. In most studies, it is suggested that due to the antioxidant role of ghrelin, it decreases testicular damages caused by various factors, such as hyperthermia, cryptorchidism and cadmium toxicity (Kheradmand, 2014;Kheradmand, Alirezaei, & Dezfoulian, 2015;Kheradmand, Dezfoulian, & Alirezaei, 2012;Kheradmand, Dezfoulian, Alirezaei, & Hadian, 2014). In this study, the effects of ghrelin on total antioxidant capacity, lipid peroxidation, sperm parameters and fertility of CP-treated mice has been studied.…”
Section: Introductionmentioning
confidence: 92%